Roots of a Degree 7 Polynomial

Algebra Level 4

The polynomial equation f a ( X ) = X 7 + 5 X 5 4 X 4 + 5 X 3 9 X 2 + X + a = 0 f_a(X) = X^7 + 5X^5 - 4X^4 + 5X^3 - 9X^2 + X + a \; = \; 0 (where a R a \in \mathbb{R} ) has roots α a , 1 , α a , 2 , α a , 3 , α a , 4 , α a , 5 , α a , 6 , α a , 7 \alpha_{a,1},\,\alpha_{a,2},\,\alpha_{a,3},\,\alpha_{a,4},\,\alpha_{a,5},\,\alpha_{a,6},\,\alpha_{a,7} . If g ( X ) g(X) is the cubic polynomial g ( X ) = X 3 + 3 X 3 g(X) \; = \; X^3 + 3X - 3 consider the quantity Q ( a ) = j = 1 7 g ( α a , j ) Q(a) \; = \; \prod_{j=1}^7 g(\alpha_{a,j}) It can be shown that Q ( a ) = A a 3 + B a 2 + C a + D Q(a) \; = \; Aa^3 + Ba^2 + Ca + D for all a R a \in \mathbb{R} , where A , B , C , D A,B,C,D are integers. What is the value of A + B + C + D |A|+|B|+|C|+|D| ?

Inspiration


The answer is 73.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Patrick Corn
Sep 27, 2019

The quantity Q ( a ) Q(a) is known as the resultant R ( f a , g ) . R(f_a,g). The resultant of two polynomials is the product of the evaluations of the second polynomial on the roots of the first polynomial (counted with multiplicities). It has several nice properties, two of which are:

(1) R ( F , G ) = ± R ( G , F ) R(F,G) = \pm R(G,F) (in fact the sign is negative iff the degrees of a , b a,b are odd)

(2) If F = G Q + S F=GQ+S and G G is monic, R ( F , G ) = R ( S , G ) . R(F,G) = R(S,G).

The proofs are left as exercises; both are quite straightforward.

This gives an algorithm for computing resultants in general, and for this particular case, we only need property (2): R ( f a , g ) = R ( X + a 3 , g ) = g ( 3 a ) = a 3 + 9 a 2 30 a + 33. R(f_a,g) = R(X+a-3,g) = g(3-a) = -a^3+9a^2-30a+33. So the answer is 73 . \fbox{73}.

Mark Hennings
Sep 26, 2019

Note first that f a ( X ) = ( X 4 + 2 X 2 X 1 ) g ( X ) + X + a 3 f_a(X) \; = \; (X^4 + 2X^2 - X - 1)g(X) + X + a-3 If the zeroes of g ( X ) g(X) are u 1 , u 2 , u 3 u_1,u_2,u_3 , then we obtain Q ( a ) = j = 1 7 g ( α a , j ) = j = 1 7 k = 1 3 ( α a , j u k ) = k = 1 3 j = 1 7 ( α a , j u k ) = k = 1 3 f a ( u k ) = k = 1 3 ( u k + a 3 ) = k = 1 3 ( 3 a u k ) = g ( 3 a ) = 33 30 a + 9 a 2 a 3 \begin{aligned} Q(a) & = \; \prod_{j=1}^7 g(\alpha_{a,j}) \; = \; \prod_{j=1}^7 \prod_{k=1}^3 (\alpha_{a,j} - u_k) \; = \; \prod_{k=1}^3 \prod_{j=1}^7 (\alpha_{a,j} - u_k) \\ & = \; -\prod_{k=1}^3 f_a(u_k) \; = \; -\prod_{k=1}^3 \big(u_k + a - 3\big) \; = \; \prod_{k=1}^3 \big(3-a - u_k\big) \\ & = \; g(3-a) \; = \; 33 - 30a + 9a^2 - a^3 \end{aligned} so that A + B + C + D = 1 + 9 + 30 + 33 = 73 |A| + |B| + |C| + |D| = 1+9+30+33 = \boxed{73} .

@Mark Hennings Sir please can you tell me about how can i find the self energy of hollow hemisphere of Mass M and radius R. ??

A Former Brilliant Member - 1 year, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...